Japanese studies resources in selected academic libraries in Metro Manila Area - Liwanag, Porfirio G. (1999)
This study looked into the strengths and weaknesses of the library resources in relation to the success of Japanese studies programs of the seven selected academic institutions in Metro Manila. The following were the specific problems of the study: 1) what are the perceptions of the faculty, students and librarians in the seven schools covered in this study regarding the Japanese studies collection in their own libraries; 2) do they share or differ in their perceptions; 3) are the Japanese studies collection in these seven schools strong or do they need improvement; and 4) what is the status of the Japanese studies collection of these seven schools?